New Student Study Orientation (OSMB) Containment of Student Independent Character Education - Agus Prasetya; Suparti; Ani Anjarwati (Universitas Pendidikan Ganesha, 2024)
This research was motivated by the low mastery and understanding of catalog books by new students. Supported by the difficulties experienced by new students in following academic tutorials and administrative services. The research objective is to analyze administrative/academic services. This type of research is qualitative research. The methods used to collect data are interviews, observation, documents and questionnaires. The subjects of this research were all students at one university. The instrument used in data collection was a questionnaire sheet. The data analysis technique uses descriptive statistical analysis of the results of questionnaire collection. The results of the research show that New Student Study Orientation activities provide smooth implementation of mastery tutorials and understanding of catalog books which can increase learning motivation. Having a catalog book can make it easier for students to receive information and the ins and outs of the University. With this research, it is necessary to carry out a more structured and focused approach in learning orientation for new students in order to strengthen and improve their independent learning character.